Exploring students’ algebraic thinking in generational activities and their difficulties - Dian Permatasari; Raekha Azka; Haya Fikriya (Universitas Islam Negeri (UIN) Mataram, 2021)
[English]: Generational, transformational, and global meta-level are three typical activities of algebraic thinking students engage in school. Several studies show that students involve more in the generational activity than the other activities. However, some students still have difficulties solving problems in the generational activity. Therefore, this study focused on the generational activity, aiming to analyze student's algebraic thinking and difficulties in the generational activity. It involved ninety-five 7th-grade students given an initial test to measure their abilities in the generational activity. The analysis of students’ answers and interviews follow three steps; data condensation, data display, and drawing and verifying conclusions. This study indicates that, in the generational activity, the students can generalize statements from patterns better than forming statements and equations containing an unknown quantity. Students’ difficulties in the generational activities, including (1) understand the problems and turn them into mathematical forms and (2) generalize the patterns to the nth term. These are due to the students’ incomprehension of the relationships of some conditions in the given problems and understanding of the meaning of variables. [Bahasa]: Kegiatan generasional, transformasional, dan meta-level global adalah tiga kegiatan berpikir aljabar yang dilakukan siswa di sekolah. Beberapa penelitian sebelumnya menunjukkan bahwa siswa lebih banyak terlibat dalam kegiatan generasional dibandingkan kegiatan berpikir aljabar lainnya. Namun, terdapat beberapa siswa yang mengalami kesulitan dalam menyelesaikan masalah pada kegiatan generasional. Oleh karena itu, penelitian ini akan difokuskan pada kegiatan generasional, dengan tujuan menganalisis pemikiran aljabar siswa dalam aktivitas generasional dan kesulitan yang dialami siswa. Penelitian ini melibatkan 95 siswa kelas 7 yang mengikuti tes awal untuk mengukur kemampuan dalam kegiatan generasional. Jawaban siswa dan hasil wawancara dianalisis melalui tiga tahap, yaitu kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Hasil penelitian ini menunjukkan bahwa dalam kegiatan generasional, siswa dapat mengeneralisasi pernyataan dari pola lebih baik daripada membuat pernyataan dan persamaan yang mengandung variabel. Siswa menunjukkan berbagai kesulitan dalam kegiatan generasional, diantaranya (1) memahami masalah dan mengubahnya menjadi bentuk matematis dan (2) menggeneralisasikan pola suku ke-n. Hal ini disebabkan siswa tidak memahami hubungan beberapa kondisi dalam masalah yang diberikan dan arti variabel.